2013
DOI: 10.1136/gutjnl-2013-305490
|View full text |Cite
|
Sign up to set email alerts
|

Barrett's oesophagus: epidemiology, cancer risk and implications for management

Abstract: Although endoscopic surveillance of patients with Barrett's oesophagus has been widely implemented, its effectiveness is debateable. The recently reported low annual oesophageal adenocarcinoma risk in population studies, the failure to identify most Barrett's patients at risk of disease progression, the poor adherence to surveillance and biopsy protocols, and the significant risk of misclassification of dysplasia all tend to undermine the effectiveness of current management, in particular, endoscopic surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 214 publications
2
87
0
4
Order By: Relevance
“…The progression of Barrett's epithelium to adenocarcinoma again occurs in a well-established stepwise fashion in which the epithelium will first develop areas of low-grade dysplasia, which progresses to high-grade dysplasia and cancer. The risk of developing esophageal adenocarcinoma is very low [between 0.05-0.5% per year for nondysplastic metaplasia (15)] but increases steeply as the epithelium progresses from normal epithelium to low-grade and high-grade dysplasia.…”
Section: Esophageal Epithelial Pathophysiology the Development Of Bamentioning
confidence: 99%
See 1 more Smart Citation
“…The progression of Barrett's epithelium to adenocarcinoma again occurs in a well-established stepwise fashion in which the epithelium will first develop areas of low-grade dysplasia, which progresses to high-grade dysplasia and cancer. The risk of developing esophageal adenocarcinoma is very low [between 0.05-0.5% per year for nondysplastic metaplasia (15)] but increases steeply as the epithelium progresses from normal epithelium to low-grade and high-grade dysplasia.…”
Section: Esophageal Epithelial Pathophysiology the Development Of Bamentioning
confidence: 99%
“…This intestinal metaplasia is called Barrett's esophagus and is a precursor lesion for the development of adenocarcinoma. Population-based studies have shown that Barrett's esophagus is present in 0.5-1.5% of the Western population (15). The progression of Barrett's epithelium to adenocarcinoma again occurs in a well-established stepwise fashion in which the epithelium will first develop areas of low-grade dysplasia, which progresses to high-grade dysplasia and cancer.…”
Section: Esophageal Epithelial Pathophysiology the Development Of Bamentioning
confidence: 99%
“…As outcomes are better when this cancer is treated early, endoscopy surveillance of individuals with the precursor Barrett's esophagus is undertaken to identify individuals who might benefit from early intervention. However, the annual rate of progression to cancer is reported to range from 0.12 to 0.4% [3], so the cost effectiveness of Barrett's esophagus surveillance has been questioned [4]. If less invasive detection tools such as a reliable blood test can be developed, then it might be possible to reduce dependence on endoscopy surveillance in high risk individuals, or more cost effective surveillance strategies might be developed.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of BE also increases with age [ 31 , 32 ]. With few exceptions, BE is rarely found in the young (in men below age 20, in women below age 40), African Americans, Asians, or women [ 31 ]. Other associated clinical risk factors include the presence of a hiatal hernia [ 21 ], obstructive sleep apnea [ 33 ], possibly diets low in fruit, and cigarette smoking [ 34 ].…”
Section: Risk Factors For Be and Strategies To Identify People To Bementioning
confidence: 97%